Pencapaian Peranan BKK dalam Penyaluran Lulusan Teknik Pengelasan di SMK DIY - Darunnajah Darunnajah; Putut Hargiyarto (Department of Mechanical Engineering Education, 2018)
This research aims to study the achievement of Special Labor Market's roles in the distribution of the welding study program graduates through the management process (planning, organizing, actuating, and controlling), and the obstacles that occurred. This research also study students' perception of the Special Labor Market (BKK) work program. The methods of this research is descriptive research. The instruments for data collection are questionnaire, interviews, and documentation. Data were analyzed using descriptive qualitative analysis. The research samples are the 5 leaders of BKK and 117 class XII students of welding study program. Result of the research indicate the following scores of the management process aspects: planning 85,6%, organizing 78,3%, actuating 80,3%, and controlling 93,1%. The distribution that have been carried out still puts the workforce out of their field of expertise. The obstacles that occurred during the distribution are: graduates are not ready to work out of their hometown or the parents did not give permission for them to work outside their hometown. The overall graduates' perception towards the implementation of labor market work program related to graduates is in the category of